The Origin of the Universe: Big Bang to God Theory - Dastagiri M.B. (European Scientific Journal, ESJ, 2018)
The universe is full of mystical things. Since ages, the belief that God became the Universe is a theological doctrine that has been developed. Evolutionary biologists and Modern scientists still believes in Big Bang theory. Many thinkers, theologians, philosophers, and scientists are unable to confirm the exact process of the origin of the universe. Hence, this paper focuses on analyzing the history of theologians, mythologists, philosophers, cosmologists and scientists research evidences, insights, theories, and rationales to find out about the origin of the universe. The study uses metaanalysis of universe origin scriptures, research, insights, and bibliographies which was put forth by theologians, philosophers, cosmologists, and scientists. The study found that as per Bhagavad-Gita, God is the source of all spiritual, intellectual, and material world. In 1996, Pastor Bob Burridge of the Genevan Institute for Reformed Studies reveals that as per Christian theology, God becoming the universe is not accordant with it. In the 1940s, Charles Hartshorne identified pandeism as a possible model of God’s nature as God is capable of changing. In 2001, Scott Adams surmised that an omnipotent God annihilated himself in the Big Bang. This is considered as per mythologist’s world created from dead deity physical substances. All Catholic scientists reported that God’s light and love revealed his creation. Physicist Bernard Haisch in his book entitled “The God Theory” concluded that the deity became the universe. Alan Dawe's (2011) book titled “The God Franchise” concludes that human knowledge is a briefly separated piece of God’s skill. Raphael Lataster (2013), Australian religious studies Scholar, projected that "Pandeism is the future God-concept of all". There is a long list of Catholic scientists who in their quest for learning maintained God at the origin of all existence. Theology and mythology proofs are not conforming with both science and philosophy. The Evolving God concept is also a wrong idea of metaphysics. If it is so, man would have been found under developed state. Jafree Ozwald explains that based on human request, the universe is not able to fulfill it but God does. The universe is not God. God is God. The study concludes that God created the universe from nothing and He is yet to manifest Himself. God is a supernatural power and has a divine holy nature that is omnipresence, omnipotence, and omniscience. The study suggests that the sharing of knowledge, debate, discussions, and consensus based on their evidences and perceptions among theologists, philosophers, mythologists, and scientists on the universe origin is a future task.